The Primitive Call Flow Served by Multi-access Lines System with Queue Leaving Calls - Pilkauskas, V.; Rindzevicius, R. (Elektronika ir Elektrotechnika, 1997)
There is analysed multi-access line delay system with queue leaving calls in two modes: analytic and simulation. The call service quality indicators have been determinated in analytic form. A specific system model is created including a description of the model. Some modeling results are presented.